New Chronological Constraints for the Late Pleistocene Fossil Assemblage and Associated Breccia from Ngalau Sampit, Sumatra. (3rd December 2021) - Duval, Mathieu; Westaway, Kira; Zaim, Jahdi; Rizal, Yan; Aswan,; Puspaningrum, Mika Rizki; Trihascaryo, Agus; Albers, Paul C. H.; Smith, Holly E.; Drawhorn, Gerrell M.; Price, Gilbert J.; Louys, Julien
We provide the first numerical age constraints for the palaeontological assemblage and associated sediment from Ngalau Sampit, Sumatra, one of M. Eugène F.T. Dubois' noted sites that he excavated in 1889, and of which we present a transcript of his unpublished report. A combination of U-series, Electron Spin Resonance (ESR) and Luminescence (pIR-IRSL) methods was employed. The three tooth samples yield 1σ consistent combined U-series/ESR ages (mean age of 105 ± 9 ka, 1 s.d.), supporting the chronological integrity of the fossil assemblage at Ngalau Sampit. Three breccia samples yield internally 1σ consistent pIR-IRSL age estimates (mean age of 93 ± 6 ka, 1 s.d.), suggesting that the breccia may represent one single depositional event. All these results are compatible with the U-series age estimates previously obtained on post-depositional carbonate formations. We cannot exclude that the existing, and systematic, age difference between ESR and pIR-IRSL methods ( 12 ka on average) may reflect the difference in the dated events (death of the animals vs. sediment burial). However, this apparent deviation is most likely not significant (mean ages are in close agreement a 1σ) and results from the existing uncertainty around the evaluation of the gamma dose rate, which partly arises from the absence of in situ dosimetry. Despite this uncertainty, all the numerical ages consistently and systematically correlate the breccia and associated fossil assemblage to MIS 5 (a finer correlation to sub-stages within MIS 5 would most likely be too speculative at this stage). Ngalau Sampit represents only the third site from the Pandang Highlands to be radiometrically dated, after Lida Ajer and Ngalau Gupin, and the second site explored and recorded by Dubois to have associated dates. Finally, Ngalau Sampit is the only site in Sumatra that chronologically correlates to MIS 5, and thus with the regionally important site of Punung in Java.